Blau aus der Waschküche: Wege einer Farbe nach Äthiopien - Marx, Annegret (Aethiopica, 2001)
In traditional Ethiopian paintings a shining blue is observed. An analysis of four objects from the Museum Haus Völker und Kulturen in St. Augustin shows that they were painted with laundry blue. This substance is of varying composition, and has contained synthetic ultramarine since 1830. Laundry blue was of daily use and carried by travellers and missionaries. It was widely used by painters because of its shining colour and good technical properties. In this article the most likely paths by which synthetic ultramarine could have reached Ethiopia are described. This can be shown to have taken place several decades before 1900, the date that has been hitherto assumed to mark the introduction of synthetic colours. The German Zander was probably the first painter in Ethiopia to decorate a church (Därasge Maryam) with synthetic ultramarine in 1852.